PERAN BADAN PENANGGULANGAN BENCANA DAERAH (BPBD) KABUPATEN KAMPAR DALAM PENCEGAHAN KEBAKARAN HUTAN DAN LAHAN TAHUN 2021-2022 - Rahmadhina, Riska Aulya; Febrina, Rury (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Forest and land fire prevention is an effort made to prevent and reduce factors that can cause forest and land fires. The Kampar Regency Regional Disaster Management Agency is a regional agency that carries out disaster management support functions. The problem in this study is that the role of the Kampar Regency Regional Disaster Management Agency has not been optimal because the area of burned land in Kampar Regency increased in 2022, while the number of cases decreased compared to 2021. The purpose of this study is to describe the role of the Kampar Regency Regional Disaster Management Agency in the prevention of forest and land fires in 2021-2022. The research approach used is a qualitative approach. The type of research is descriptive. The location of the research is in Kampar Regency and the Kampar Regency Regional Disaster Management Agency. The types of data and sources of research data are divided into primary data with data collection techniques, namely interviews from informants and secondary data in the form of documents related to research problems. The data collection technique is by means of interviews and documentation. The data analysis was carried out by qualitative analysis. The result of this study is that the Kampar Regency BPBD has carried out its functions and duties in accordance with article 7 paragraph 5 letter a of the Kampar Regent Regulation Number 65 of 2016 concerning the Position, Composition, Organization, Duties and Functions and Work Procedures of the Kampar Regency Regional Disaster Management Agency. The Kampar Regency BPBD has also carried out five forms of roles, namely as policy creators, coordinators, facilitators, implementers, and accelerators. In carrying out this role, the Kampar Regency BPBD collaborates and coordinates with all relevant stakeholders in achieving efforts to prevent forest and land fires. Keywords : Role, BPBD, Prevention